Effect of geranylgeranylacetone on the protection of retinal ganglion cells in a mouse model of normal tension glaucoma. Issue 10 (October 2016) - Dong, Zhenyu; Shinmei, Yasuhiro; Dong, Yoko; Inafuku, Saori; Fukuhara, Junichi; Ando, Ryo; Kitaichi, Nobuyoshi; Kanda, Atsuhiro; Tanaka, Kohichi; Noda, Kousuke; Harada, Takayuki; Chin, Shinki; et al.
Abstract: Glaucoma is characterized by axonal degeneration of retinal ganglion cells (RGCs) and apoptotic death of their cell bodies, and lowering intraocular pressure is associated with an attenuation of progressive optic nerve damage. Nevertheless, intraocular pressure (IOP) reduction alone was not enough to inhibit the progression of disease, which suggests the contribution of other factors to the glaucoma pathogenesis. In this study, we investigated the cytoprotective effect of geranylgeranylacetone (GGA) on RGCs degeneration using a normal tension glaucoma (NTG) mouse model, which lacks glutamate/aspartate transporter (GLAST) and demonstrates spontaneous RGC and optic nerve degeneration without elevated intraocular pressure (IOP). Three-week-old GLAST +/− mice were given oral administration of GGA at 100, 300, or 600 mg/kg/day or vehicle alone, and littermate control mice were given vehicle alone for 14 days, respectively. At 5 weeks after birth, the number of RGCs was counted in paraffin sections of retinal tissues stained with hematoxylin and eosin. In addition, retrograde labeling technique was also used to quantify the number of RGC. Expression and localization of heat shock protein 70 (HSP70) in retinas were evaluated by reverse transcription polymerase chain reaction and immunohistochemistry, respectively. Activities of caspase-9 and -3 in retinas were also assessed. The number of RGCs of GLAST +/− mice significantly decreased, as compared to that of control mice. RGC loss was significantly suppressed by administration of GGA at 600 mg/kg/day, compared with vehicle alone. Following GGA administration, HSP70 was significantly upregulated together with reduction in the activities of caspase-9 and -3. Our studies highlight HSP70 induction in the retina is available to suppress RGC degeneration, and thus GGA may be applicable for NTG as a promising therapy.